Clinical, Diagnostic and Histological Findings Involving Cheek Teeth Hypercementosis in Nine Horses. (December 2022) - Brown, James A.; Murphy, Brian G.; Clapp, Kemba S.; LaDouceur, Elise E. B.
Hypercementosis is infrequently reported to affect the cheek teeth of horses and presents as mineral deposits either attached (peripheral) or solitary ovoid (nodular) structures in the tooth bearing region. There is overlap between radiological and histological appearance of hypercementosis, cementoma, and equine odontoclastic tooth resorption and hypercementosis (EOTRH). The clinical presentation, imaging features, surgical management, and histological findings of nine horses that presented for dental lesions and associated hypercementosis of cheek teeth are reported. Horses were 4-15 years old and presented for either nasal discharge or facial swelling. Peripheral and nodular mineral structures were identified using radiographs or computed tomography in six and three horses, respectively. Eight of nine cases involved maxillary cheek teeth. Of six cases with peripheral hypercementosis, three had enlargement of the apical cross-sectional area that was greater than the coronal cross-sectional area thus preventing extraction along the normal eruption pathway and necessitating sectioning (two cases) and repulsion. Nodular hypercementosis lesions were extracted in three of the four cases. Post-extraction complications occurred in five cases; four cases required additional procedures. All horses returned to their intended use, ie riding or pasture. Histology of extracted dental and proliferative mineral material revealed hypercementosis characterized by large sheets of eosinophilic matrix with lacunae (usually empty; presumed artifact) and frequent, irregular, basophilic cement lines. All cases had evidence of chronic inflammation, such as caries, chronic fractures and/or pulpitis. The findings of this case series share many features with previous published descriptions of cementoma and with histological findings of hypercementosis lesions of EOTRH. Further investigation into differentiation of these entities is warranted.